양안 시효율과 삶의 질: 국민건강영양 조사자료의 분석 - 김수한(Soo Han Kim); 추헌구(Hun Gu Choo); 윤이나(Ie Na Yoon) (Daihan angwa haghoi jabji, 2016)
목적: 제5기 국민건강영양조사 자료를 토대로 양안 시효율이 삶의 질과 연관성이 있는지 확인해 보고자 하였다. 대상과 방법: 제5기 국민건강영양조사에서 시력, 시야 검진 및 설문검사를 완료한 녹내장 혹은 녹내장 의증인 5,244명을 대상으로 연구하였다. 최대교정시력과 시야검사 결과를 토대로 양안 시효율을 계산하였으며, 삶의 질 평가는 EuroQoL 5D (EQ-5D) 설문을 이용하였다. 또한 시효율과 최대교정시력 두 변수를 이용하여 삶의 질에 대한 설명력을 비교하였다. 일원분산분석과 편상관분석을 이용하여 이들 간의 연관관계를 분석하였다. 결과: 녹내장 혹은 녹내장 의증인 대상자들에서 시효율과 좋은 눈의 최대교정시력 둘 다 EQ-5D 설문의 모든 지표에서 통계적으로 유의한 차이를 나타내었다(p＜0.005). 나이, 성별, 소득, 교육, 직업, 배우자 여부, 자택 소유 여부를 통제한 후 분석한 삶의 질과의 관계에서 시효율은 상관계수 +0.040의 양의 상관관계가 있었으며(p=0.006), 좋은 눈의 최대교정시력은 상관계수 -0.044인 음의 상관관계가 있음을 확인할 수 있었다(p=0.002). 결론: 녹내장 혹은 녹내장 의증인 대상자들에서 시효율도 삶의 질과 통계학적으로 유의한 상관관계가 있었다. 좋은 눈의 최대교정시력뿐만 아니라 양안 시효율도 삶의 질에 영향을 미치는 것을 확인한 바, 시효율 역시 삶의 질에 대한 평가에 좋은 변수가 될 것으로 사료된다. 녹내장과 관련이 없는 일반인의 경우 추가적인 연구가 필요할 것으로 보인다. Purpose: To analyze the association of visual efficiency and quality of life using data from the fifth Korea National Health and Nutrition Examination Survey (KNHANES V). Methods: The present study included 5,244 glaucoma or glaucoma suspect subjects who completed a visual acuity test, visual field test and health-related questionnaire from the KNHANES V. Visual efficiency was calculated using best corrected visual acuity and visual field test. Quality of life was assessed with EuroQoL 5D (EQ-5D). Visual efficiency was compared with best corrected vision of the better eye to evaluate the relationship with quality of life. One-way analysis of variance (ANOVA) and partial correlations analysis were used to analyze the associations between factors. Results: Both visual efficiency and best corrected visual acuity of the better eye were significantly different with all EQ-5D parameters (p < 0.005). After controlling for age, gender, income, education, spouse and house ownership, visual efficiency showed a positive correlation coefficient of +0.040 (p = 0.006) with the quality of life and the best corrected visual acuity of the better eye showed negative correlation coefficient of -0.044 (p = 0.002) with the quality of life. Conclusions: Visual efficiency was associated with the quality of life. Not only visual acuity but also visual efficiency would be a valuable parameter when considering the quality of life. Further studies are needed to evaluate non-glaucomatous populations. KCI Citation Count: 0